Phra Kilanupatthaka and End-of-Life Carein Thailand’s Palliative Care System: An Integrative Literature Review: Phra Kilanupatthaka and End-of-Life Carein Thailand’s Palliative Care System: An Integrative Literature Review - Puanfai, Supattra; Thitavisiddho (Wongsai), PhraWisit; Suttikul, Nawara (RATANABUTH JOURNAL, 2026)
This is an integrative literature review, following the framework of Whittemore and Knafl, that aims to (1) analyze the role of Phra Kilanupatthaka in caring for dying monks; (2) synthesize Buddhist knowledge supporting palliative care; (3) examine ethical tensions between Vinaya discipline and medical constraints; and (4) propose an integrative model for incorporating Phra Kilanupatthaka into Thailand’s palliative care system. A systematic search yielded 38 academic and research documents published between 2012 and 2023 that met the inclusion and quality-appraisal criteria. The synthesis found that Phra Kilanupatthaka possess knowledge and skills consistent with palliative care principles across four dimensions: physical, psychological, social, and spiritual care. This role is formally recognized by the National Monk Health Charter B.E. 2560 and the 70-hour training curriculum. However, standardized frameworks and monk-specific screening tools remain lacking, and unresolved ethical tensions persist between strict adherence to the Vinaya and medical necessity. The new contribution of this article is the “Kilanupatthaka Palliative Integration Model (KPIM),” a conceptual proposal that, for the first time, links a Buddhist value foundation, palliative-care competencies, and a supporting network system into a single framework intended as a starting point for further field testing.